High-frequency scattering by objects buried in lossy media. - Bertoncini, F.
The uniform geometrical theory of diffraction (UTD) is extended so that it can be used to calculate the scattering from an object buried in a lossy medium. First, the accuracy of this high frequency method is examined by comparing numerical results for the scattering by a polygonal cylinder in a lossy medium of infinite extent with calculations based on a method of moments (MoM) solution. Next, the more difficult scattering problem of a polygonal cylinder in a lossy half space is treated. The UTD solution for the unbounded region is employed together with the fields of rays introduced by the interface between air and the lossy medium to obtain expressions for the scattered field in air and in the lossy medium
Keywords: HF scattering; MoM solution; TE polarization; TM polarization; UTD solution; Air; Buried objects; High-frequency scattering; Infinite polygonal cylinder; Lossy half space; Lossy media; Method of moments; Scattered field; Unbounded region; Uniform geometrical theory of diffraction